Study on Thermal Conductivity of Carbon Fiber / Resin Composite Modified with Graphene Nanoplatelets. (August 2020) - Liu, Fangbiao; Wang, Danyong; Li, Shuhu; Wei, Huazhen; Chen, Yiwei; Liu, Juncong
Abstract: A method for calculating thermal conductivity of graphene/carbon fiber reinforced resin composites (GnP-CFRP) was established basing on the Mori-Tanaka program in the DIGIMAT software. The influence of grapheme nanoplatelets (GnP) on the thermal conductivity of composites has been simulated and experimentally verified. The results show that the thermal conductivity of GnP-CFRP increased with the increase of GnP content, and when the GnP content is too high, the increasing rate of thermal conductivity decreases gradually. In addition, the maximum prediction error of the simulation calculation method in this paper is within 7.27%, which is in good agreement with the actual situation.